Electrophysiological characteristics and long-term outcome of substrate-based catheter ablation for left posterior fascicular ventricular tachycardia targeting fragmented antegrade Purkinje potentials during sinus rhythm. Issue 3 (4th January 2023) - Wei, Hui-Qiang; Liao, Zili; Liang, Yuanhong; Fang, Xianhong; Liao, Hongtao; Deng, Hai; Wei, Wei; Huang, Yingjie; Liu, Yang; Liu, Fangzhou; Lin, Weidong; Liang, Jackson J; et al.
Abstract: Aims: The aim of this study was to investigate the electrophysiological characteristics and long-term outcome of patients undergoing substrate-based ablation of left posterior fascicular ventricular tachycardia (LPF-VT) guided by targeting of fragmented antegrade Purkinje potentials (FAPs) during sinus rhythm. Methods and results: This study retrospectively analysed 50 consecutive patients referred for ablation. Substrate mapping during sinus rhythm was performed to identify the FAP that was targeted by ablation. FAPs were recorded in 48 of 50 (96%) patients during sinus rhythm. The distribution of FAPs was located at the proximal segment of posterior septal left ventricle (LV) in two (4.2%) patients, middle segment in 33 (68.8%) patients, and distal segment in 13 (27.1%) patients. In 32 of 48 (66.7%) patients, the FAP displayed a continuous multicomponent fragmented electrogram, while a fragmented, split, and uncoupled electrogram was recorded in 16 (33.3%) patients. Entrainment attempts at FAP region were performed successfully in seven patients, demonstrating concealed fusion and the critical isthmus of LPF-VT. Catheter ablation targeting at the FAPs successfully terminated the LPF-VT in all 48 patients in whom they were seen. Left posterior fascicular (LPF) block occurred in four (8%) patients after ablation. During a median follow-up period of 61.2 ± 16.8 months, 47 of 50 (94%) patients remained free from recurrent LPF-VT. Conclusion: Ablation of LPF-VT targeting FAP during sinus rhythm results in excellent long-term clinical outcome. FAPs were commonly located at the middle segment of posterior septal LV. Region with FAPs during sinus rhythm was predictive of critical site for re-entry.